2011
DOI: 10.1038/labinvest.2010.151
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines induce small intestine and liver injury after renal ischemia or nephrectomy

Abstract: Patients with acute kidney injury (AKI) frequently suffer from extra-renal complications including hepatic dysfunction and systemic inflammation. We aimed to determine the mechanisms of AKI induced hepatic dysfunction and systemic inflammation. Mice subjected to AKI [renal ischemia reperfusion (IR) or nephrectomy] rapidly developed acute hepatic dysfunction and suffered significantly worse hepatic IR injury. After AKI, rapid peri-portal hepatocyte necrosis, vacuolization, neutrophil infiltration and pro-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
155
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(167 citation statements)
references
References 45 publications
12
155
0
Order By: Relevance
“…Renal IRI rapidly caused marked hepatic vacuolization evident sinusoidal dilatation, and vascular congestion. These results were supported by other researchers [1,7] who stated that liver cell injury and hepatocyte death (necrotic and apoptotic) occurred following renal IRI as a result of oxidative stress and decreased its antioxidant capacity. In addition, some investigators attributed liver cell damage to the microvascular reorganization of hepatic parenchyma [33].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Renal IRI rapidly caused marked hepatic vacuolization evident sinusoidal dilatation, and vascular congestion. These results were supported by other researchers [1,7] who stated that liver cell injury and hepatocyte death (necrotic and apoptotic) occurred following renal IRI as a result of oxidative stress and decreased its antioxidant capacity. In addition, some investigators attributed liver cell damage to the microvascular reorganization of hepatic parenchyma [33].…”
Section: Discussionsupporting
confidence: 83%
“…The significant increase in serum urea and creatinine confirmed the occurrence of renal dysfunction and the altered serum AST and ALT indicated remote liver injury. Renal IRI induces an inflammatory response, which results in the formation of reactive oxygen species (ROS) that augments local tissue damage or affects organs remote from the site of IRI [1,5,6,9]. Several previous studies [16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 It is shown that cytokines may have a role in small intestine and liver injury after renal ischemia. 34 Bilateral kidney IR injury leads to an increase in both systemic and cardiac TNF-a. 35 A recent study identified that ischemic AKI induces lung endothelial apoptosis via TNFR1 and limited data suggest a role for systemic elevation of inflammatory cytokines and apoptosis; however, the mechanism was not expressed clearly.…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating evidence that ischemia activates the immune system, and that this activation is both local and systemic, and involves the release of toxic cytokines, including TNF. 10,11 Additionally, this release of TNF may activate protective mechanisms in the form of superoxide dismutase. 12 This unique case provides the opportunity to discuss the organogenesis of the renal system.…”
Section: Discussionmentioning
confidence: 99%